2q37 Deletions in Patients With an Albright Hereditary Osteodystrophy Phenotype and PTH Resistance - Elli, Francesca Marta; de Sanctis, Luisa; Madeo, Bruno; Maffini, Maria A.; Bordogna, Paolo; Pirelli, Arianna; Arosio, Maura; Mantovani, Giovanna (Frontiers in Endocrinology, 2019)
Pseudohypoparathyroidism (PHP) is a rare endocrine disorder derived from the defective activation of the cAMP pathway by the parathyroid hormone secondary to GNAS molecular defects. PHP subtypes are defined by the presence/absence of specific clinical/biochemical features. PHP1A is characterized by resistance to multiple hormones with features of Albright hereditary osteodystrophy (AHO), while pseudopseudohypoparathyroidism (PPHP) is characterized by AHO in the absence of PTH resistance. Small subsets of PHP and PPHP patients without known molecular defects have been re-diagnosed as being affected by the brachydactyly-mental retardation syndrome (BDMR), also known as the AHO-like syndrome. This study aimed to analyse 24 PHP1A and 51 PPHP patients without a molecular diagnosis for the presence of BDMR-associated 2q37 deletions to improve the differential diagnosis and to identify features that might help to avoid a misdiagnosis. Molecular investigations identified 4 deletions in 4 unrelated patients. The affected patients showed a combination of the most pathognomonic AHO features. Of note, 3 of the patients also displayed mild PTH resistance, and none of the patients developed ectopic ossifications. Our work confirmed the rarity of the misdiagnosis of BDMR in PHP patients through the identification of 4 patients bearing a 2q37 deletion in a cohort of 73 PHP patients (5.3%). Three patients with the deletion presented a PHP1A phenotype in the absence of any BDMR-specific findings. Further studies on larger case series are needed to elucidate the overlap between these clinical entities and to allow the early identification of patients.